Students’ perception of social presence in facebook. - Jamil, Nur Jannah (Areadiscover, 2022)
Acquiring social presence promotes the degree of salience between two people using communication medium and development of interpersonal relationship. Nonetheless, research on social presence elements in social network system, such as Facebook, normally focuses on Facebook as general; considerably less is known about the relation between specific activities in Facebook towards the five dimensions in social presence: social respect, social sharing, social identity, open mind, and intimacy. Hence, this study uncovered students’ perception of online social presence with relation to their experience, average time spent per day and activities done in Facebook by utilizing the questionnaire adapted from the study by Sung and Mayer (2012). The respondents of this study were a group of students who have similar experience of participating in academic discussion in Facebook on computer subject. Two-ways communication in Facebook, as in chatting, commenting, and sending message correlated positively with all dimensions in social presence. Those Facebook usages are also most frequently used by students, along with several other activities that signify students’ interests to acknowledge themselves with any update or news from the society they choose as Facebook friends. Students might have regularly encountered with social presence instances through their vast experience on using Facebook with major usage of more than 2 years and minimum average of 1 hour per day. Hence, that could justify the high social presence the respondents believe they have perceived. These findings suggest that Facebook can be considered as a promising platform to utilize social presence to the most if the availability of its various tools and activities that support social interaction are put into the best practice to nurture student’s social presence in online learning.